Innovation and creativity in entrepreneurship: a bibliometric analysis - Anis Sya'bania; Andika Wulan Febriani; Bambang Supeno; Sudarmiatin Sudarmiatin (Universitas Islam Lamongan, 2022)
This literature study focuses on the impact of innovation and creativity on entrepreneurship. The method used is bibliometric literature study analysis which is analyzed by VOSviewer software. The VOSviewer analysis technique was used to analyze the articles that had been compiled through the Scholar database which were taken as a reference for researchers. The findings of this article were referenced from 2017 to 2021 with a total of 26 articles from 50 articles found for analysis. Next, the researcher clarified and visualized using VOSviewer software to analyze co-authorship, co-occurrence, and citation. This study provides a reliable reference for further research on the topic, allowing for more in-depth research on topics such as innovation and creativity in business. Innovation and creativity are essential to the success of any business. Innovators and creative thinkers can generate new ideas and identify new business opportunities. Every man or woman can be creative and innovative for all ages. The ability to create new and different things by carrying out innovative and creative processes is a key factor in achieving different values.